(3bQI GdCHUGQ aj SjQI GdeTaY GdeNJGQs - (3YHO GdYRjR Hf YHO GdYRjR GddeWj,J (B880 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3hHYO aGYde Cf NjQ ebJai aSejJg HbQI GdCHUGQ ai SjQI GdeTaY GdeNJGQ eQJHkG Ydi GdCHhGH s
(3BNQgG (B:s
(3cGf dg ef GdKjGH GKfi YTQ Ydi GdPi fbdg Cgd GdSjQ s
(3GdfSNI HgG MhGTs
(3fSNI HgG JQeje hbO VGYJ HYV cdeGJgG hYdjgG MhGTis
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdJGQjNs